Upaya penatalaksanaan nyeri dada pada pasien congestive heart failure di rsud dr. Soehadi prijonegoro - Setyo Muharrom, Bagus; , Ns. Arief Wahyudi Jadmiko, M.Kep (2016)
Deaths due to non-communicable diseases (NCDs) is dominated by four groups of diseases with proportions that cardiovascular disease (CVD) that includes heart disease - stroke -peripheral vascular disease 64%, cancer 21%, respiratory diseases chronic 12%, and diabetes mellitus 3% , CHF (congestive heart failure) disease the cause of death dominated the first which is 36 million people worldwide, or 64% of all global deaths. Congestive Heart Failure (CHF) is a condition when the heart is not able to sustain adequate circulation for the needs of the body, although the filling pressure normal venous blood, with common complaints of pain. Pain due to an imbalance of oxygen supply to the heart. Some pain management that can be done to overcome the pain is deep breathing relaxation technique, your technique imagery, progressive relaxation techniques, environmental management. The main strategy in the specific nursing enhances a sense of comfort for patients who are experiencing pain, non-pharmacological. As we know that nurses do not have the authority provide an analgesic.This study aimed to understand the effect of nursing care in patients with a diagnosis of Congestive Heart Failure Congestive Heart Failure (CHF) in the ward tulip dr. Soehadi Prijonegoro Sragen The method used was descriptive case study approach, is to perform nursing care in heart failure patients ranging from assessment, intervention, implementation, and evaluation of nursing. After the 3x24-hour nursing care for heart failure patients with acute pain problem the problem is resolved. The influence non-pharmacological therapy in reducing pain scale. Acute pain nursing problem is resolved, the patient and family is indispensable for the success of nursing care. The influence nonpharmacological therapy in reducing pain scale.